Investigation of Method of Addition of Surfactant to the Pressure Leaching of Nickel-Containing Pyrrhotite Concentrates - A. V. Tarasov; E. M. Timoshenko (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
The results of laboratory, bench-scale and semi-commercial investigations of a method for adding surfactant (technical-grade lignosulphonate) to the process of pressure leaching of nickel-containing pyrrhotite concentrates have been discussed. Lt has been demonstrated that feeding of technical-grade lignosulphonate distributed along the length of an autoclave ensures a reduction in its requirement by a factor of 1.5 to 2 as compared with single-point feeding; it also results in a decrease by 5% in the unit requirement of metallized iron-bearing precipitator in the process of non-ferrous metals precipitation and reduces by 0.05 to 0.1% (abs.) the nickel and copper contents in the tailings of the given process. Technical solutions have been proposed for commercial introduction of the process.